La fabrique des grands maîtres : apprendre à l'université ou en grande école - Olivier Marty
Two fieldworks as a university and afterwards Grande École teacher, at the master level, allow a comparison of professional practices in French educative institutions. This didactical approach of a profession, led by a researcher thinking the craft of teaching, compares: institutions, teaching and learning practices, curricula engineering and pedagogical tools. It opens crossed perspectives onto active teaching methods with project group works, digital innovation and massive professionalization of students in higher education. The research aims at a better ethnographical knowledge of two kinds of French educative institutions and ends up with a political project of cooperation, within the European higher education area fostering harmonization.